Franciszka Próchnickiego "instrukcja" programowa i metodyczna - Gajak-Toczek, Małgorzata (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2003)
Franciszek Próchnicki belongs to the outstanding representatives of grammar school Polish studies during the last quaretr of a century after the partition of the country. He was born in 1847 at Brzeżany in Eastem-Galicia, after graduation from the Lvov University in 1873 he became a Secondary-School-teacher, at first at his home townand later at Lvov, where he acted as headmaster of the Secondary School Nr. V froml891 till to 1905 when he went. Franciszek Próchnicki was also a member of the Higher-School-Teachers’Society, which held over teachers from popular and Secondary Schools, founded lending libraries for young people, determined on teaching schedules and attached the highest importance to programs for the Polish language.He was known as author of a number of instructions for Polish-language for Secondary School of the former Galicia, especially the Guide for Polish Language Studies (1885) was the base for all programs of this subject untill 1918.As a didactician of literature Próchnicki set induction based on a wellfoundcd knowlage of literary texts. It was very important opinion. He took sides against the generally adopted acroamatic methods conected with Herbart’s views of education. This progressive yeacher confirmed that learning by heart was a process leading to uncreative attitiude towards, precluding individual things.In the history of Polish language studies during the partion of poland Próchnicki renderd a great service by making capital of any oportunity which might to Galicia in order to set Polish science on the national track.All his life Próchnicki devoted to teacher’s occupation.He died at Lvov in 1911.